Baseline, retest, and post-injury profiles of auditory neural function in collegiate football players. (1st September 2021) - Rauterkus, Grant; Moncrieff, Deborah; Stewart, Gregory; Skoe, Erika
Abstract: Objectives: Recent retrospective studies report differences in auditory neurophysiology between concussed athletes and uninjured controls using the frequency-following response (FFR). Adopting a prospective design in college football players, we compared FFRs before and after a concussion and evaluated test-retest reliability in non-concussed teammates. Design: Testing took place in a locker room. We analysed the FFR to the fundamental frequency (F0) (FFR-F0) of a speech stimulus, previously identified as a potential concussion biomarker. Baseline FFRs were obtained during the football pre-season. In athletes diagnosed with concussions during the season, FFRs were measured days after injury and compared to pre-season baseline. In uninjured controls, comparisons were made between pre- and post-season. Study Sample: Participants were Tulane University football athletes ( n  = 65). Results: In concussed athletes, there was a significant group-level decrease in FFR-F0 from baseline (26% decrease on average). By contrast, the control group's change from baseline was not statistically significant, and comparisons of pre- and post-season had good repeatability (intraclass correlation coefficient = 0.75). Conclusions: Results converge with previous work to evince suppressed neural function to the FFR-F0 following concussion. This preliminary study paves the way for larger-scale clinical evaluation of the specificity and reliability of the FFR as a concussion diagnostic. Highlights: This prospective study reveals suppressed neural responses to sound in concussed athletes compared to baseline. Neural responses to sound show good repeatability in uninjured athletes tested in a locker-room setting. Results support the feasibility of recording frequency-following responses in non-laboratory conditions.